1998
DOI: 10.1159/000057378
|View full text |Cite
|
Sign up to set email alerts
|

High-Glucose Media Enhance the Responsiveness of Tubular Cells to Growth Promoters: Effect on Lysosomal Cathepsins and Protein Degradation

Abstract: Nephromegaly is a prominent feature of diabetic nephropathy and predominantly reflects increased renal tubule mass, mostly due to hypertrophy. To elucidate pathogenetic factors involved, we studied the effects of high glucose (HG) alone, and in combination with hormones/growth promoters: angiotensin II (10–7 M); parathyroid hormone (10–7 M); insulin-like growth factor-1 (10–7 M), or transforming growth factor-β1 (TGF-β1, 10 ng/ml) in a renal cell line (LLC… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
11
0

Year Published

2002
2002
2009
2009

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 28 publications
1
11
0
Order By: Relevance
“…11 These results may be linked to changes in transforming growth factor-␤ (TGF-␤) expression, which is upregulated in diabetes and other kidney disease states 12 and may be upregulated in hypertension as a result of increased stretching forces [13][14][15] brought about by the hypertensive state. Recent studies have shown that lysosomal activity may be affected by increased TGF-␤ levels, 16 and its role in albuminuria induction may be further supported by the fact that ACE inhibitors and decreasing albuminuria are correlated with decreased TGF-␤ levels, 17 which leads to the hypothesis to be tested in this study.…”
mentioning
confidence: 71%
See 1 more Smart Citation
“…11 These results may be linked to changes in transforming growth factor-␤ (TGF-␤) expression, which is upregulated in diabetes and other kidney disease states 12 and may be upregulated in hypertension as a result of increased stretching forces [13][14][15] brought about by the hypertensive state. Recent studies have shown that lysosomal activity may be affected by increased TGF-␤ levels, 16 and its role in albuminuria induction may be further supported by the fact that ACE inhibitors and decreasing albuminuria are correlated with decreased TGF-␤ levels, 17 which leads to the hypothesis to be tested in this study.…”
mentioning
confidence: 71%
“…A possible linkage factor is the role of TGF-␤. This growth factor is known to decrease lysosomal enzyme activities, 16 with increased production of TGF-␤ by mesangial cells when subjected to stretching forces brought about by high intraglomerular pressures. [13][14][15] Our results suggest that TGF-␤ production in hypertension may be playing a role in albuminuria through this mechanism, with results showing decreased lysosomal activity with an upregulation of TGF-␤, resulting in increased intact albuminuria irrespective of changes in glomerular permeability and net albumin excretion.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, the increased albumin excretion rate may be due to either a glomerular charge-selectivity defect or to decreased tubular catabolism. Recent studies suggest that an increased glomerular pressure may increase albumin excretion rate by affecting glomerular cell metabolism: stretching of mesangial cells by increased pressure (38 -40) increases the production of TGF-␤, which may impair the lysosomal enzyme activity in tubular cells (41,42). This leads to increased urinary albumin excretion independently of an altered glomerular permselectivity, as shown in a model of hypertension-induced albuminuria (42).…”
Section: Discussionmentioning
confidence: 99%
“…Upregulation of TGF-β has also been demonstrated in stroke-prone spontaneously hypertensive rats [13](possibly due to expression by mesangial cells associated with stretching forces [14, 15, 16]brought about by high intra-glomerular pressure). Although TGF-β has long been noted for its fibrogenic potential [12, 17, 18], recent studies suggest that TGF-β also influences lysosomal enzyme activity [19]. This may provide an interesting new mechanism for how TGF-β may be involved in the onset of albuminuria in both diabetes and in hypertension.…”
Section: Introductionmentioning
confidence: 99%